(untitled) (MATEMATIKA, 2012)
In [1] Titchmarsh proved some theorems on the classical Fourier transform of functions satisfying conditions related to the Cauchy-Lipschitz conditions on the Euclidean space R. In this paper we extend one those theorems for the Bessel transform for function on half-line [0,1) in a weighted Lp-metric are studied with the use of Bessel generalized translation. Keywords: Bessel operator; Bessel transform; Bessel generalized translation. 2010 Mathematics Subject Classification: 42B10; 42A38; 42B37.